The abative effect: A new term to describe the action of antecedents that reduce operant responding - Laraway, Sean (2002)
Behavior-analytic terminology concerning the so-called inhibitory effect of operant antecedents lacks precision. The present paper describes the problem with current nomenclature concerning the effects of antecedent events that reduce operant responding and offers a solution to this problem. The solution consists of adopting a new term, abative, for the effect in question. This paper suggests that the new term has several advantages over terms currently used and that adopting this term will yield a variety of practical and theoretical benefits, including, but not limited to, a more consistent vocabulary to describe antecedent—behavior relations.